Evaluasi Kebijakan Pengelolaan Sumber Daya Alam Di Indonesia: Tantangan Dan Peluang Untuk Masa Depan - Siti Khadijah Hidayat; Sri Sundari; Marisi Pakpahan (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
Natural resource management in Indonesia brings complex conflicts involving stakeholders and the use of natural resources. In particular, the natural resource management paradigm needs to be changed to deal with oil palm-related conflicts in border areas, which have the potential to increase tensions between countries. This research aims to determine the effectiveness of natural resource management policies in Indonesia's border regions, with a focus on conflicts related to palm oil. The research method used is qualitative with a literature study approach, involving in-depth analysis of various sources of information such as scientific journals, government reports and other related literature. The research results show that conflicts related to natural resources tend to be triggered by social and economic inequality, as well as neglect of environmental problems. The importance of managing conflict efficiently using models such as negotiation and facilitation is apparent. Involving local actors, including the community, in making policies has a crucial role in ensuring the suitability of policies with community aspirations. Indonesia has adopted sustainable policies, but barriers such as perception and lack of coordination between levels of government still need to be overcome. Therefore, this research suggests creative and forward-thinking solutions, including civil service reform, increasing ecotourism, and developing active community participation as prospects towards natural resource management.